2014
DOI: 10.1136/annrheumdis-2014-eular.4145
|View full text |Cite
|
Sign up to set email alerts
|

FRI0078 European Pilot Study on Vitamin D Serum Levels and Disease Activity in Rheumatoid Arthritis Patients

Abstract: Background Several studies have demonstrated low 25(OH)D3 serum levels, which could influence pathogenesis and clinical outcomes of immune-mediated diseases such as rheumatoid arthritis (RA) (1,2). Objectives In order to investigate the necessity to implement specific vitamin D patient related outcomes we performed a pilot European multicentre study, involving individuals from different countries/latitudes, to explore 25(OH)D3 serum levels and their possible correlation with disease activity and related outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…Our findings are in concordance with the findings by Kostoglou-Athanassiou, et al [12], Rossini, et al [10], Haque and Bartlett [11]. Also, Welsh, et al [30], Cutolo, et al [31] and Kerr and colleagues [32] stated that 25-OH vitamin D deficiency is linked with increased disease activity in RA. However, other studies did not find a significant correlation between 25-OH vitamin D and RA activity scores [16,33,34].…”
Section: Discussionsupporting
confidence: 82%
“…Our findings are in concordance with the findings by Kostoglou-Athanassiou, et al [12], Rossini, et al [10], Haque and Bartlett [11]. Also, Welsh, et al [30], Cutolo, et al [31] and Kerr and colleagues [32] stated that 25-OH vitamin D deficiency is linked with increased disease activity in RA. However, other studies did not find a significant correlation between 25-OH vitamin D and RA activity scores [16,33,34].…”
Section: Discussionsupporting
confidence: 82%
“…This is in concordance with previous observations wherein RA patients have significantly low level of vitamin D than healthy individuals 9,10 . Also, our data suggested that age factors could not be correlated with vitamin D levels in arthritic subjects suggesting that vitamin D level might be independent of age.…”
Section: Comparison Between Vitamin D Levels In Normal and Arthritic supporting
confidence: 82%
“…Some group of investigators found negative association between serum vitamin D level and RA disease 9,10 . In contrast, we could not find any correlation between vitamin D levels in normal and arthritic subjects.…”
Section: Comparison Between Vitamin D Levels In Normal and Arthritic mentioning
confidence: 99%
“…And this result supported by Craig, et al 21 which failed to discover a statistically significant association between vitamin D3 and DAS28 following multivariate adjustments in recent-onset rheumatoid arthritis patients. Cutolo, et al 22 found a remarkable negative correlation between vitamin D3 and DAS28 in summer only in Southern European (Italian) patients and in winter in northern European (Estonian) patients, but no significant differences with respect to vitamin D3 values between Estonian and Italian RA patients and their controls. Research which doesn't agree with my result in disease activity and vitamin D3 are in an open-labeled randomized trial comparing triple disease-modifying antirheumatic drug (DMARD) therapy and 500 IU vitamin D3 + calcium combination versus triple DMARD and calcium alone by Gopinath et al, low levels of serum vitamin D3 were related to moderate-high disease activity in and supplementation of 500 IU of vitamin D3 daily was given to previously DMARD-naïve patients with early rheumatoid arthritis along with triple DMARD therapy showed significantly higher pain relief (50%vs.…”
Section: Resultsmentioning
confidence: 99%